'Now I want to use it to learn more': using mobile phones to further the educational rights of the girl child in Kenya. Issue 2 (4th May 2018) - Zelezny-Green, Ronda
ABSTRACT: The Kenyan Constitution states that all children have a right to education. However, over the past 15 years, girls in Kenya have been unable to exercise this right consistently – particularly at the secondary school level. During this same period, there has been greater access to digital technologies within Kenya, and the use of mobile phones has increased exponentially. Girls have contributed to this uptake, using mobile phones for multiple purposes including leisure, socialising, and education. However, the Kenyan education policy landscape is fraught with tensions that often curtail the potential for girls to use mobile phones, thus impacting their access to various rights – including that of education. This article draws on eight months of data from a research study that focused on the after-school mobile media practices of a group of secondary school girls in Nairobi. It critically reflects on how government policies affect these experiences, and explores a creative approach to how girls can use mobile phones to realise their rights in a digital age.